Analisis Eksploratori Tweet Saham Studi Eksploratori Twitter IDX (@IDX_BEI) - Dewi Anggraini; Yuli Harwani (Jurnal Pasar Modal dan Bisnis, 2019)
Purpose- The purpose of this research is 2, that is, exploration in utilizing microblogging twitter data to obtain stock market sentiment attribute, secondly, finds the attribute of Indonesian stock market sentiment from twitter Indonesia Stock Exchange @IDX_BEI. Methods- This research is an exploratory study with longitudinal data. In exploratory research, the data used are primary data obtained by collecting Twitter social network account tweets, tweet samples are determined based on the period span July to December 2016. Finding- This research has obtained the stock market sentiment attribute obtained from @idx_bei, but the results are still minimal because the tweets delivered in @idx_bei are still general regarding IHSG and IPO only.